Cultivating Ice over Time: On the Idea of Timeless Knowledge and Places in the Himalayas - Gagné, Karine (Anthropologica, 2017)
Assumptions that local communities have an endogenous capacity to adapt to climate change stemming from time-tested knowledge and an inherent sense of community that prompts mobilisation are becoming increasingly common in material produced by international organisations. This discourse, which relies on ahistorical and apolitical conceptions of localities and populations, is based on ideas of timeless knowledge and places. Analysing the water-place nexus in Ladakh, in the Indian Himalayas, through a close study of glacier practices as they change over time, the article argues that local knowledge is subject to change and must be analysed in light of changing conceptions and experiences of place by the state and by local populations alike.